Physical activity after breast cancer - conditions for practicing sports - Filarecka, Agnieszka; Leksowski, Łukasz; Biernacki, Maciej; Jęchorek, Michał (Journal of Education, Health and Sport, 2022)
Physical activity is a vital part of your lifestyle. Reports on the positive effects of physical activity are widely discussed in the literature. However, there are also drawbacks to physical activity. One of the contraindications is neoplastic disease. Such reports pretend to reduce the activity in cancer patients. The aim of the work is to present a method of modifying physical activity in women after breast cancer treatment in order to consolidate the rehabilitation therapy and the prevention of treatment-related disorders. The paper proposes the procedure and conditions for the implementation of physical activity.